Assessment of Urban Plantations Spatial-Temporal Structure - Martynova, Maria (Journal of Environmental Accounting and Management, 2026)
The spatial-temporal distribution of vegetation within an urban environment is known as ``green space’’ and is a fundamental component of an urban environment. The study aims to assess the spatial-temporal structure of plantations in Ufa, including using satellite images. The studies covered urban forests, plantations of general use in Ufa. It has been determined that most of the Ufa urban forestry territory is occupied by deciduous plantations - 90.6% of the forested area, conifers - 4.2%. The plantations of Ufa’s common areas in 2019 amounted to 1,236.5 hectares, of which parks prevail - 66.6%. The location of plantings of common areas in the city’s districts is uneven: objects are most widespread in the Kirovsky district (37.7%). The correlation dependence between green spaces and the number of residents by administrative districts was r = 0.43 ± 0.03. The increase in the area of plantations of common areas is confirmed by the analysis of the land area by types of Ufa’s underlying surface for 1987-2018, carried out based on the calculation of the ARVI vegetation index based on Landsat-5 and Landsat-8 satellite images. A significant increase in the area occupied by tree and shrub vegetation + 10,875.2 hectares was revealed, with a reduction in the surface type ``open soil’’ - -2,666.07 hectares and ``without vegetation’’ - -1,393.83 hectares (t _calc. = - 0.002; t _0.05 tab. = 2.306). The transformation of the urban area over 30 years is due to increased green spaces in common areas and the construction of roads, buildings, and structures.